Backstepping Adaptive Control of DFIG-Generators for Variable-Speed Wind Turbines (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2014)
In this paper, we present a nonlinear robust control of active and reactive power by the use of the technique Backstepping a double-fed asynchronous generator (DFIG) system incorporated in a wind. The power transfer between the stator and the network is carried out by acting on the rotor via a bidirectional signal converter.Initially, a control strategy of the MPPT asynchronous double fed generator is presented. Thereafter, a new control technique for wind systems is presented. This control scheme is based on an adaptive pole placement control strategy integrated to a Backstepping control scheme. The overall stability of the system is shown using Lyapunov technique. The performance and robustness are analyzed and compared by simulation based Matlab / Simulink software.